Clumped Isotope Calibration Data from Breitenbach et al. 2018, reprocessed as part of a community calibration effort - Petersen, Sierra; Breitenbach, Sebastian; Hodell, David (IEDA: EarthChem Library, 2019)
Abstract: Clumped isotope calibration data from 14 published studies were compiled and reprocessed from the base level (raw voltages or small delta values) using updated IUPAC parameters defining the composition of international standards (VPDB, VSMOW) and 17O fractionation, updated theoretical equilibrium values, and newly calculated acid digestion fractionation (AFF) corrections. This EarthChem dataset archives all reprocessed data originally from Breitenbach et al. (2018, GCA), presented in the synthesis publication. Other Description: S.V. Petersen, W.F. Defliese, C. Saenger, M. Daëron, K.W. Huntington, C.M. John, J.R. Kelson, S.M. Bernasconi, A.S. Coleman, T. Kluge, G.A. Olack, A.J. Schauer, D. Bajnai, M. Bonifacie, S.F.M. Breitenbach, J. Fiebig, A.B. Fernandez, G.A. Henkes, D. Hodell, A. Katz, S. Kele, K.C. Lohmann, B.H. Passey, M.Y. Peral, D.A. Petrizzo, B.E. Rosenheim, A. Tripati, R. Venturelli, E.D. Young, and I.Z. Winkelstern, (2019), "Effects of Improved 17O Correction on Inter-Laboratory Agreement in Clumped Isotope Calibrations, Estimates of Mineral-Specific Offsets, and Temperature Dependence of Acid Digestion Fractionation." Geochemistry, Geophysics, Geosystems.